Lung omics signatures in a bronchopulmonary dysplasia and pulmonary hypertension-like murine model - Shrestha, Amrit Kumar (Am J Physiol Lung Cell Mol Physiol, 2018)
Bronchopulmonary dysplasia (BPD), the most common chronic lung disease in infants, is associated with long-term morbidities, including pulmonary hypertension (PH). Importantly, hyperoxia causes BPD and PH; however, the underlying mechanisms remain unclear. Herein, we performed high-throughput transcriptomic and proteomic studies using a clinically relevant murine model of BPD with PH. Neonatal wild-type C57BL6J mice were exposed to 21% oxygen (normoxia) or 70% oxygen (hyperoxia) during postnatal days (PNDs) 1–7. Lung tissues were collected for proteomic and genomic analyses on PND 7, and selected genes and proteins were validated by real-time quantitative PCR and immunoblotting analysis, respectively. Hyperoxia exposure dysregulated the expression of 344 genes and 21 proteins. Interestingly, hyperoxia downregulated genes involved in neuronal development and maturation in lung tissues. Gene set enrichment and gene ontology analyses identified apoptosis, oxidoreductase activity, plasma membrane integrity, organ development, angiogenesis, cell proliferation, and mitophagy as the predominant processes affected by hyperoxia. Furthermore, selected deregulated proteins strongly correlated with the expression of specific genes. Collectively, our results identified several potential therapeutic targets for hyperoxia-mediated BPD and PH in infants.